2018
DOI: 10.14715/cmb/2018.64.10.1
|View full text |Cite
|
Sign up to set email alerts
|

Role of statin as inducer of Hmox-1 system in treatment of preeclampsia

Abstract: Preeclampsia is the major cause of both maternal and neonatal morbidity and mortality. Its insidence remains high and the management has not been established yet because its etiology and pathophysiological are still poorly understood. Theories regarding etiopathogenesis and management of preeclampsia have been postulated yet it remains controversial. Placental ischemic and angiogenic imbalance are suggested to be predisposing factors of preeclampsia. It is thereby targeted in prevention of preeclampsia. Unfort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 23 publications
0
8
0
1
Order By: Relevance
“…A study of metformin showed it was able to prevent PE, reducing the production of sFlt-1 and sEng and ameliorating endothelial dysfunction through effects on mitochondria [ 202 ]. The protein statin exerts a protective effect on endothelial cells through induction of Hmox-1 expression and inhibition of sFlt-1 release, along with its antioxidant properties [ 203 ].…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…A study of metformin showed it was able to prevent PE, reducing the production of sFlt-1 and sEng and ameliorating endothelial dysfunction through effects on mitochondria [ 202 ]. The protein statin exerts a protective effect on endothelial cells through induction of Hmox-1 expression and inhibition of sFlt-1 release, along with its antioxidant properties [ 203 ].…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…preeclampsia is based on animal studies showing that pravastatin (3-hydroxy-3-methylglutaryl coenzyme-A-reductase inhibitor) has a protective role at the uteroplacental interface and in endothelial cells 21,24 . It was initially proposed by Ahmed et al that pravastatin protects vascular endothelial cells by inducing the expression of Hemeoxygenase-1 (HO-1), and as such inhibiting cytokine mediated release of the anti-angiogenic factors sFlt-1 and sEng 4,[25][26][27] . Decreased levels of sFlt-1 and sEng will increase the free PlGF and VEGF in placental and endothelial cells.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The rationale to use statin as a drug for preeclampsia is based on animal studies showing that pravastatin (3-hydroxy-3-methylglutaryl coenzyme-A-reductase inhibitor) has a protective role at the uteroplacental interface and on vascular cells (17,20,21). Pravastatin may protect endothelial cells, by inducing the expression of HO-1 and as such inhibiting cytokine mediated release of the anti-angiogenic factors sFlt-1 and sEng (18,19,(22)(23)(24)(25)(26)(27).…”
Section: Accepted Manuscriptmentioning
confidence: 99%